Hybrid nanoparticles for the topical delivery of norfloxacin for the effective treatment of bacterial infection produced after burn. (19th May 2017) - Dave, Vivek; Kushwaha, Kriti; Yadav, Renu Bala; Agrawal, Udita
Abstract: The present study was designed to investigate the solubility and penetrability of norfloxacin after the topical application of developed lipid–polymer hybrid nanoparticle (LPN) formulation. The core shell of the LPNs formulation was composed of poly (lactic-co-glycolic acid) that is highly lipophilic in nature, thus control the release of drug. The developed formulations were characterised for size, shape (transmission electron microscopy [TEM], scanning electron microscopy [SEM], and atomic force microscopy), entrapment efficiency, Fourier transform infra-red (FTIR) spectroscopy, differential scanning calorimetry (DSC) and thermo gravimetric analysis (TGA). Moreover, in vitro skin permeation studies were performed to determine release profile of the drug. Norfloxacin loaded nanoparticles retained there antimicrobial efficacy against Staphylococcus aureus and Pseudomonas aeruginosa . Stability study was suggested that the suitable storage condition should be at 4 ± 2 °C/60 ± 5% RH for the LPNs. Therefore, these nanoparticles showed a safe and effective long-lasting approach for long treatment of bacterial infections due to burn.